The Role of Ethical Values in Preventing Marital Disputes and Building Harmonious Families - Mukti, Oscharil Aji; Shobahiya, Mahasri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Marriage is a vital institution that fosters a harmonious family structure. However, the high divorce rate is a concerning phenomenon, with the primary causes often related to communication problems, infidelity, and differing values. Ethical values, such as honesty, empathy, and mutual respect, are believed to play a crucial role in preventing marital discord and strengthening communication between partners.This study aims to investigate the role of ethical values in preventing marital discord and building family harmony, with a focus on the application of ethical principles in the Indonesian cultural context. The methodology used in this study is a qualitative approach with a systematic literature review, analyzing various relevant scientific articles to assess the impact of the application of ethical values on marital and family harmony. The results of the study indicate that the application of strong ethical values in marital relationships can improve effective communication, prevent conflict, and strengthen relationship stability. Couples who share the same ethical values tend to have higher levels of marital satisfaction and are better able to manage conflict constructively. In conclusion, the application of ethical values in marriage has a positive impact on preventing conflict and maintaining family harmony, especially in societies with social and cultural norms that emphasize the importance of moral responsibility between partners. This study also suggests the importance of an approach that integrates ethical values into social policy to create stable and harmonious families.